2017
DOI: 10.1177/0306624x17706891
|View full text |Cite
|
Sign up to set email alerts
|

Matricide in Ghana: Victims, Offenders, and Offense Characteristics

Abstract: At present, scholarship on matricide across many regions of the non-Western world is lacking. For instance, in Ghana, despite the intermittent, yet recurrent, availability of media reports describing matricidal acts over the past quarter century, no existing study has systematically analyzed matricidal killings in the West African nation. To contribute to the literature and extend knowledge about matricide and other forms of lethal violence in Ghana, this article presents the results of an analysis of 21 matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
(88 reference statements)
2
20
0
Order By: Relevance
“…The study draws on online media reports on vigilantism from the period 2001 to 2018. The study approach was, thus, modelled after the method used in recent studies on some social and criminal issues in Ghana, for example, matricides, gang rape, suicide, and incest, inter alia (for example, (Adinkrah 2014, 2018; Quarshie et al . 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The study draws on online media reports on vigilantism from the period 2001 to 2018. The study approach was, thus, modelled after the method used in recent studies on some social and criminal issues in Ghana, for example, matricides, gang rape, suicide, and incest, inter alia (for example, (Adinkrah 2014, 2018; Quarshie et al . 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Heide (2017) also points out that evidence of mental illness can be found in all types of parricide offenders (such as depression in severely abused and psychopathy in dangerously antisocial offenders), but that it can only be considered a direct reason for homicide in the severely mentally ill offender type. Indeed, international research has shown schizophrenia and delusional disorders to be the most common mental health diagnoses in parricide offenders followed by adjustment disorder and personality disorder (antisocial and borderline; Adinkrah, 2017, 2018; De Borba‐Telles et al, 2017; Lennings, 2003; Raymond, Léger, & Lachaux, 2015; Sahin et al, 2016). Even though often used, Heide's typology has not yet been, according to the authors’ knowledge, examined using a data‐driven bottom‐up approach.…”
Section: Introductionmentioning
confidence: 99%
“…The use of newspapers to study murder has been an accepted methodology, especially in countries where there are no national criminal justice databases (Adinkrah, 2014(Adinkrah, , 2017(Adinkrah, , 2018 or during historical periods where newspapers constituted the most accessible centralised repository of information about crime in a community (Sharpe, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Cases were retrieved by searching the phrases “murder,” “family murder” and “parricide.” This type of methodology has been successfully used by a number of previous researchers (Adinkrah, 2017; Boots & Heide, 2006; Fegadel & Heide, 2017; Govender, 2015). The use of newspapers to study murder has been an accepted methodology, especially in countries where there are no national criminal justice databases (Adinkrah, 2014, 2017, 2018) or during historical periods where newspapers constituted the most accessible centralised repository of information about crime in a community (Sharpe, 2012). Due to the violent nature of the act, family‐related murders often receive extensive media coverage (Adinkrah, 2014; Liem & Reichelmann, 2014); it was therefore possible to identify family‐related murders using this open source methodology (Parkin & Gruenewald, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation